"Emotional Support Won't Cure Cancer": Reasons People Give for Not Providing Emotional Support. Issue 1 (1st January 2019) - Ray, Colter D.; Manusov, Valerie; McLaren, Rachel M.
Abstract : A major stressor faced by many people in their lifetime is a cancer diagnosis; however, cancer patients often report instances of people they know who never communicated emotional support regarding their diagnosis. The present study explored reasons potential supporters gave for not providing emotional support to others they knew who had recently been diagnosed with cancer. Sixteen reasons emerged and were categorized across four higher-order categories: Reasons related to the source, the recipient, the relationship, and the context. People providing source- and recipient-based reasons had higher relational closeness scores, and closeness was also related to greater expectation for providing support.